Serum thyroglobulin elevation after needle aspiration of the lymph nodes: the predictive value for detecting metastasis in papillary thyroid cancer patients – a pilot study. Issue 31 (August 2019) - Hong, Chae Moon; Jeong, Ju Hye; Son, Seung Hyun; Lee, Chang-Hee; Jeong, Shin Young; Lee, Sang-Woo; Lee, Jaetae; Ahn, Byeong-Cheol
Abstract : Abstract: Ultrasonography (USG)-guided fine needle aspiration (FNA) is widely used for diagnosis of lymph node (LN) metastasis in papillary thyroid cancer (PTC). However, FNA cytology sometimes shows inconclusive results. Recently, the measurement of thyroglobulin (Tg) in FNA washout fluid (aspirate-Tg) has been widely adopted, but there are some difficulties in the preparation of the sample and standardization of the procedure. Here, we examined serum Tg after FNA as a new predictive marker for LN metastasis of PTC. We performed USG-guided FNA cytology and examined aspirate-Tg in PTC patients showing suspicious metastatic LNs during follow-up. We measured baseline serum thyroid stimulating hormone (TSH), Tg, and Tg antibody levels before FNA, and serum Tg level within an hour after FNA. We defined aspirate-Tg level above 0.9 ng/mL as positive, and a 30% increase in serum Tg level after FNA compared to the baseline as elevation of serum Tg. Twenty-two patients were included in our study. Nine patients (40.9%) showed elevation of Tg level after FNA, and the mean value of Tg elevation was 24.8 ± 48.0 ng/mL. Among these 9 patients, 8 were diagnosed with PTC and 1 patient showed cellular atypia on cytopathology. All these patients showed positive aspirate-Tg. Thirteen patients (59.1%) did not show elevation of Tg level after FNA. Among these patients, 2 had PTC, 2 had cellular atypia, and 9 yielded negative results for malignancy on cytopathology. Elevation of serum Tg level after FNA might have a diagnostic role for predicting LN metastasis of PTC.